(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The aim of this study was to estimate the total amount of phenolic compounds of olive trees leaves (Olea europaea L.) as Biomarker for the assessment of lead air pollution at Banias area. Olive trees were selected as the predominant species in the study area. The samples were collected from 6 locations at different distances from the vicinity of the Banias refinery (0.1, 0.5, 2, 4, 6, 10) Km. The dominated wind in the region is western - southwesterly during the winter (March) and summer (September), The control was taken from an area about 20 km from the refinery to the north-east (al-Qardahah rural). The concentration of total phenolic compounds (TPC) during the summer was (45.6-70.85) mg GAE/g dw and in the control (40.4) mg GAE/g dw, and during the winter the content of TPC was (35.6-52.9) mg GAE/g dw and in the control (25.8) mg GAE/g dw. The concentration of Lead (Pb) in unwashed leaves during the summer was (0.879 – 2.170) ppm and in the control (0.005) ppm, whilst during the winter was (0.479-1.023) ppm and in the control (0.00083) ppm. The results showed significant differences in the concentration of total phenolic compounds and lead between sites (Anova test). High concentration of total phenols and lead in the summer compared to values in winter at all sites (t-test). The results also showed a negative correlation between the concentration of total phenolic compounds and lead with the distance from the refinery of Banias. Finally, The results showed that the TPC can be used as biomarker of lead air pollution in Banias area.